EFEKTIVITAS MODEL PEMBELAJARAN AUDITORY INTELECTUALY REPETITION TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA DI SMK KESEHATAN SIDIMPUAN HUSADA - Laila Hannum Harahap (JURNAL MathEdu (Mathematic Education Journal), 2019)
abstract The aims of this study is to describe the effectiveness of applying AIR learning model on students’ mathematical critical thinking ability at the tenth grade students of SMK Kesehatan Sidimpuan Husada. This research was conducted by applying experimental (one group pre test post test design) with 24 students as the sample and they were taken by using total sampling technique. Observation and test were used in collecting the data. Based on descriptive analysis, it was found that: (a) the average of applying AIR learning model was 3.4 (very good category), (b) the average of students’ mathematical critical thinking ability before applying AIR learning model was 43.54 (fair category) and after applying AIR learning model was 84.27 (very good category). Furthermore, based on inferential statistics by using pair sample ttest, the result showed the significant value was less than 0.05 (0.000<0.05) and by using N-Gain formulation showed that g=0.72. It means, applying AIR learning model on students’ mathematical critical thinking ability had high effectiveness at the tenth grade students of SMK Kesehatan Sidimpuan Husada. Keywords:AIR learning model, mathematical critical thinking ability